Effect of protons on the mechanical response of rat muscle nociceptive fibers and neurons in vitro. (March 2015) - Hotta, Norio; Kubo, Asako; Mizumura, Kazue
Highlights: We hypothesized that protons sensitize muscular nociceptors to mechanical stimuli. The response magnitude of muscular nociceptors was increased by low pH. Their mechanical threshold was lowered by low pH. The threshold decrease by low pH was also observed in mechanically activated currents. Mechanical sensitization by protons might be involved in ischemic muscle pain. Abstract: Strong exercise makes muscle acidic, and painful. The stimulus that activates muscle nociceptors in such instance may be protons. Reportedly, however, not many afferents are excited by protons alone. We, therefore, posited that protons sensitize muscular nociceptors to mechanical stimuli. We examined effects of protons on mechanical sensitivity of muscle nociceptors by single-fiber recording from rat muscle-nerve preparations in vitro and by whole cell patch-clamp recording of mechanically activated (MA) currents from cultured rat dorsal root ganglion neurons. We recorded 38 Aδ- and C-fibers. Their response magnitude was increased by both pH 6.2 and pH 6.8; in addition the mechanical threshold was lowered by pH 6.2. Decrease in the threshold by pH6.2 was also observed in MA currents. Presently observed sensitization by protons could be involved in several types of ischemic muscle pain, and may also be involved in cardiovascular and respiratory controls during exercise.